Implementation and Acceptance of Latin Dances in Senior High School Curriculum - Daryll Jay M. Landero; Derick Vince Gadayan; Ian M. Valderama; Jayson A. Falle; Vivencio L. Calixtro Jr. (Universitas Pendidikan Indonesia (UPI), 2022)
This study is to determine how Latin dances are implemented and how students accept Latin dances as one of their core subjects. Also, this study was to highlight that there are limited studies related to the implementation and acceptance of Latin dances in the Senior high school curriculum. The study used a quantitative-correlational design and employed a complete enumeration sampling technique in selecting the respondents. The finding shows that Latin dances in the senior high school curriculum were not fully implemented and it needs to be strengthened. The acceptance of Latin dances is slightly accepted. Lastly, it was also concluded that there is a significant relationship between implementation and acceptance of Latin dance in senior high school. Thus, this research can contribute to the development of how Latin Dances teaches in Senior high school, for it provides information about the result about the implementation and acceptance of Latin dances in Senior high school curriculum.